Tibial torsion correlates with talar morphology. Issue 3 (April 2022) - Ciufo, David J.; Baker, Erin A.; Gehrke, Corinn K.; Vaupel, Zachary M.; Fortin, Paul T.
Highlights: There is a correlation between tibial torsion and talus morphology. External tibial torsion correlates with a cavovarus foot type. The talus can have a wide variation in neck-body anatomy. Axial anatomy of the ankle is important for preoperative planning. Abstract: Background: There is limited literature on axial rotation of the ankle or variations in anatomy of the talus. We aim to evaluate the rotational profile of the distal tibia and its relationship to talus morphology, radiographic foot-type, and tibiotalar tilt in arthritic ankles. Methods: Preoperative imaging was reviewed in 173 consecutive patients with ankle arthritis. CT measurements were used to calculate tibial torsion and the talar neck-body angle (TNBA). Tibiotalar tilt and foot-type were measured on weightbearing plain radiographs. Results: Measurements indicated mean external tibial torsion of 29.2 ± 9.1˚ and TNBA of 35.2 ± 7.5˚ medial. Tibiotalar tilt ranged from 48˚ varus to 23.5˚ valgus. A moderate association between increasing external tibial torsion and decreasing TNBA was found ( ρ  =  − 0.576, p   <  .0001). Weak relationships were found between external tibial torsion and varus tibiotalar tilt ( ρ  = −0.239, p   =  .014) and plantarflexion of the talo-first metatarsal angle ( ρ  = −0.218, p   <  .025). Conclusion: We observed a statistically significant correlation between tibial torsion and morphology of the talus, tibiotalar tilt, and first ray plantarflexion. This previously unreported association may provide information regarding the development of foot and ankle deformity and pathology. Level of evidence: Level III.